Motility of Amphistegina lobifera throughout the 4-week BEA experiment - Christiane Schmidt; Diana N Puerto Rueda; Moritz Nusser; Clinton A Oakley; Xavier Pochon; Marleen Stuhr; Débora Raposo; Simon K Davy (PANGAEA, 2025)
This dataset records the motility of the foraminifera species Amphistegina lobifera observed over the 4-week Bleaching Ecophysiology Assessment (BEA) experiment. It includes data on the amount of foraminifera attached to the walls of the culturing jar and potential changes in motility over time in response to experimental conditions.
In: Schmidt, C et al. (2025): Menthol-DCMU bleaching experiments on two foraminifera species, Amphistegina lobifera and Sorites orbiculus [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.974618 (DOI registration in progress)